2011
DOI: 10.1002/ajmg.b.31241
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in CNTNAP2 alters brain function during linguistic processing in healthy individuals

Abstract: Language impairments are a characteristic feature of autism and related autism spectrum disorders (ASDs). Autism is also highly heritable and one of the most promising candidate genes implicated in its pathogenesis is contactin-associated protein-like 2 (CNTNAP2), a gene also associated with language impairment. In the current study we investigated the functional effects of variants of CNTNAP2 associated with autism and language impairment (rs7794745 and rs2710102; presumed risk alleles T and C, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 38 publications
1
100
1
1
Order By: Relevance
“…One study in (Ross et al, 1999) suggested decreased PLA2 activity in putamen for schizophrenia patients. It was also shown in (Whalley et al, 2011) that the association between CNTNAP2 gene and brain activity exists in the right inferior frontal gyrus in healthy individuals during a language task, which may indicate the potential risk to mental illness.…”
Section: Biological Implicationsmentioning
confidence: 94%
“…One study in (Ross et al, 1999) suggested decreased PLA2 activity in putamen for schizophrenia patients. It was also shown in (Whalley et al, 2011) that the association between CNTNAP2 gene and brain activity exists in the right inferior frontal gyrus in healthy individuals during a language task, which may indicate the potential risk to mental illness.…”
Section: Biological Implicationsmentioning
confidence: 94%
“…Mice with a Caspr2 deletion show analogous behavioral defects and symptoms [142]. Interestingly, common variants of the CNTNAP2 gene in healthy individuals are associated with abnormal language processing and are a risk factor for autism [143]. Caspr2 antibodies act by disrupting axonal potassium currents.…”
Section: Anti-vgkc-complex Encephalitismentioning
confidence: 99%
“…Moreover, it has become clear that, just as observed for other measures of cognition and behavior, the effect sizes of common genomic variants are small and require large samples to achieve sufficient power (Thompson et al 2014). Imaging genetic studies of language are beginning to be performed, with intriguing results; again, to take the example of CNTNAP2, common variants of this gene are reported to be associated with language-related brain activations (Whalley et al 2011), event-related potentials (Kos et al 2012), and altered structural connectivity (Dennis et al 2011) in the healthy brain. However, note that most studies in this area have used small sample sizes, yielding low power and high risk of type I error (false-positive findings).…”
Section: Universality Variability and The Era Of Personal Genomicsmentioning
confidence: 99%